Deficiency of Rbpj Leads to Defective Stress-Induced Hematopoietic Stem Cell Functions and Hif Mediated Activation of Non-canonical Notch Signaling Pathways - Lakhan, Ram; Rathinam, Chozha V. (Frontiers in Cell and Developmental Biology, 2021)
Deregulated notch signaling has been associated with human pathobiology. However, functions of notch pathways in hematopoiesis remain incompletely understood. Here, we ablated canonical notch pathways, through genetic deletion of Rbpj, in hematopoietic stem cells (HSCs). Our data identified that loss of canonical notch results in normal adult HSC pool, at steady state conditions. However, HSC maintenance and functions in response to radiation-, chemotherapy- and cytokine- induced stress were compromised in the absence of canonical notch. Rbpj deficient HSCs exhibit decreased proliferation rates and elevated expression of p57Kip2. Surprisingly, loss of Rbpj resulted in upregulation of key notch target genes and augmented binding of Hes1 to p57 and Gata2 promoters. Further molecular analyses identified an increase in notch activity, elevated expression and nuclear translocation of Hif proteins, and augmented binding of Hif1 to Hes1 promoter in the absence of Rbpj. These studies, for the first time, identify a previously unknown role for non-canonical notch signaling and establish a functional link between Hif & Notch pathways in hematopoiesis.